Stress Degrades Prefrontal Cortex Neuronal Coding of Goal-Directed Behavior. (25th May 2016) - Devilbiss, David M.; Spencer, Robert C.; Berridge, Craig W.
Abstract: Stress, pervasive in modern society, impairs prefrontal cortex (PFC)-dependent cognitive processes, an action implicated in multiple psychopathologies and estimated to contribute to nearly half of all work place accidents. However, the neurophysiological bases for stress-related impairment of PFC-dependent function remain poorly understood. The current studies examined the effects of stress on PFC neural coding during a working memory task in rats. Stress suppressed responses of medial PFC (mPFC) neurons strongly tuned to a diversity of task events, including delay and outcome (reward, error). Stress-related impairment of task-related neuronal activity included multidimensional coding by PFC neurons, an action that significantly predicted cognitive impairment. Importantly, the effects of stress on PFC neuronal signaling were highly conditional on tuning strength: stress increased task-related activity in the larger population of PFC neurons weakly tuned to task events. Combined, stress elicits a profound collapse of task representations across the broader population of PFC neurons.